Phylogenetics of Gratioleae (Plantaginaceae) : paraphyly of Stemodia and its implications for generic circumscriptions, with insights from floral evolution - Scatigna, André Vito (2022)
Fil: Scatigna, André Vito. Universidade Estadual de Campinas; Brasil.